Media Boneka Tangan Untuk Meningkatkan Keterampilan Berbicara Anak Pada Kelompok A TK Aisiyah Bustanul Athfal Dalam Kecamatan Taliwang Kabupaten Sumbawa Barat Tahun Ajaran 2020/2021 - Nihlawati Nihlawati; Ni Komang Sri Ayu Lestari; Maria Magdalena Meo (Early Childhood Education Development and Studies (ECEDS), 2021)
The use of hand puppets to improve children's speaking skills in group A TK Aisiyah Bustanul Athfal Dalam, Taliwang District, West Sumbawa Regency, Academic Year 2020/2021. The problem discussed in this study is how to use hand puppets to improve children's speaking skills through hand puppets. The goal to be achieved in this study was to find out how far the speaking ability or speaking skills of children through Aisiyah Bustanul Athfal (ABA) Taliwang District, West Sumbawa Regency, 20 children were able to use hand puppets in their speaking skills, the rest were still shy. The research was conducted for a week and the data collected was quantitative and qualitative. Quantitative data is data obtained from the results of formative tests in each cycle. While the qualitative data is in the form of observations in each learning cycle. The data obtained is then consulted with the success criteria to find out the child's learning outcomes.